Bloodlands : Europe between Hitler and Stalin - Snyder, Timothy 1969- (Basic Books, 2010)
In this revelatory book, Timothy Snyder offers a groundbreaking investigation of Europe's killing fields and a sustained explanation of the motives and methods of both Hitler and Stalin. He anchors the history of Hitler's Holocaust and Stalin's Terror in their time and place and provides a fresh account of the relationship between the two regime